Sociological pragmatics from a hard-science perspective: a side-note to the conception of human linguistics - Wąsik, Elżbieta (Scripta Neophilologica Posnaniensia, 2018)
Sociological pragmatics from a hard-science perspective: a side-note to the conception of human linguistics